Smart App Creator–Based Learning Media as an Innovation to Improve Student Learning Outcomes for Achieving Quality Education - Shafira Ratu Sekartaji Putri Kediri; Atip Nurharini (Postgraduate, University of Mataram, 2026)
Dance is an essential component of Arts, Culture, and Crafts (SBdP) learning in primary schools, including traditional regional dances such as the Denok Semarangan dance from Semarang, Central Java. This study aimed to develop and evaluate Smart App Creato based learning media for teaching Denok Semarangan dance to improve students’ learning outcomes. The research employed a research and development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects were 31 fifth-grade students of SDN Wonosari 03, Semarang City. Expert validation showed that the media was highly feasible, with average scores of 92.00% from material experts and 88.50% from media experts. Effectiveness testing indicated significant improvements in learning outcomes. In the cognitive domain, paired t-test results showed a significant difference between pretest and posttest scores (p < 0.05), with N-Gain values of 0.65 (medium category) in the small group and 0.74 (high category) in the large group. In the psychomotor domain, students’ performance increased from 81.50% to 85.20%. In the affective domain, student attitude questionnaire results showed a positive response with an average score of 86.40%. These findings conclude that SAC-based Denok Semarangan dance learning media is effective in improving cognitive, psychomotor, and affective learning outcomes.